2012
DOI: 10.1002/syn.21621
|View full text |Cite
|
Sign up to set email alerts
|

Facilitation of fear extinction by the 5‐HT1A receptor agonist tandospirone: Possible involvement of dopaminergic modulation

Abstract: Fear extinction-based exposure treatment is an important component of psychotherapy for anxiety disorders such as posttraumatic stress disorder (PTSD). Recent studies have focused on pharmacological approaches combined with exposure therapy to augment extinction. In this study, we elucidated the therapeutic potential of the serotonin 1A (5-HT(1A) ) receptor agonist tandospirone compared with the effects of the N-methyl-D-aspartate partial agonist D-cycloserine (DCS), focusing on the possible involvement of dop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 50 publications
1
19
0
Order By: Relevance
“…These results support a role for M5Rs in maintaining and restoring previously learned CPP, possibly through the sustained activation of dopamine neurons by M5Rs [26,[49][50][51]. Previous authors have argued that dopamine neural activity is important in the learning of extinction and spontaneous recovery in different paradigms [52,53].…”
Section: Morphine Induced Similar Cpp In Both M5 Ko and Wildtype C57bsupporting
confidence: 79%
“…These results support a role for M5Rs in maintaining and restoring previously learned CPP, possibly through the sustained activation of dopamine neurons by M5Rs [26,[49][50][51]. Previous authors have argued that dopamine neural activity is important in the learning of extinction and spontaneous recovery in different paradigms [52,53].…”
Section: Morphine Induced Similar Cpp In Both M5 Ko and Wildtype C57bsupporting
confidence: 79%
“…Buspirone and other 5-HT 1A R agonists are approved for the treatment of GAD, with fair response rates [50]. In preclinical studies, 5-HT 1A R agonists are anxiolytic in animal models of general anxiety [51], prevent the adverse effects of stress [52], and enhance fear extinction [53]. Both pre-and postsynaptic 5-HT 1A Rs are coupled to various members of the G i/o protein family.…”
Section: -Ht 1a Receptorsmentioning
confidence: 99%
“…Dopamine has been implicated in many learning and memory processes, often as a mediator of memory consolidation through its role as a promoter of long-term potentiation in regions of the brain such as the mPFC (where synaptic potentiation has been found to occur and correlate with extinction learning (Saito et al, 2012)). Output neurons in the mPFC receive a large number of dopaminergic inputs from the ventral tegmental area and are thought to be involved in communicating fear inhibition learned through extinction via their excitatory projections to GABAergic interneurons in the amygdala, thereby reducing its activity and the subsequent expression of fear-related behavior.…”
Section: Pharmacotherapeutic Approachesmentioning
confidence: 99%
“…It was found that the extinction enhancements related to an increase in mPFC dopamine release, which in turn increased mPFC activity during extinction retrieval. Importantly, there was no increase in serotonin release in the mPFC (Saito et al, 2012). Finally, and perhaps paradoxically, systemic administration of sulpiride, a dopamine D2 receptor antagonist, before extinction training resulted in enhanced extinction memory retention during subsequent tests, whereas quinpirole, a D2 agonist, resulted in diminished extinction learning.…”
Section: Pharmacotherapeutic Approachesmentioning
confidence: 99%